Implementasi Algoritma Clustring K-NN Pada Klasifikasi Siswa Berprestasi - Fince Tinus Waruwu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Determining outstanding students in an educational institution is a decision made based on variables that are considered capable of determining student achievement. Therefore, in its determination, it is hoped that there will be minimal errors, so that qualified technology and techniques are needed. In determining the outstanding students, the K-NN (K-Nearest Neighbor) technique was used. K-NN is a classification technique that is able to handle an object with various patterns in a large number. This method will group the data obtained with neighboring data based on their distance. This method is often used because it is very simple and easy to understand. This research produced outstanding students at Islamic Imam Islamic boarding schools by looking at the variables used as benchmarks for students.